2001
DOI: 10.7164/antibiotics.54.239
|View full text |Cite
|
Sign up to set email alerts
|

Collinone, a New Recombinant Angular Polyketide Antibiotic Made by an Engineered Streptomyces Strain.

Abstract: Large chromosomal DNAfragments containing different parts of the putative rubromycin polyketide synthase "gene cluster were cloned and functionally expressed in S. coelicolor CH999. Expression of these clones yielded 5-10 metabolites that were not detected in S. collinus culture extracts. This paper focusses on one of the new metabolites, termed collinone, that was isolated in large quantities and purified for spectroscopic structure determination and biological screening assays. Collinone is a heavily oxidize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 34 publications
3
44
0
1
Order By: Relevance
“…strain PGA 22 to S. collinus contains sequences that are responsible for the biosynthesis of rubromycins or similar compounds, because in this group Streptomyces sp. strain PGA 64 and S. collinus, from which the genes responsible for rubromycin biosynthesis have recently been cloned (17), are known to produce rubromycins. A variety of sequences also cluster around the aureolic acid producer S. argillaceus, but it is not possible to propose boundaries for this group because there is no information about the compounds produced by the surrounding strains.…”
Section: Resultsmentioning
confidence: 99%
“…strain PGA 22 to S. collinus contains sequences that are responsible for the biosynthesis of rubromycins or similar compounds, because in this group Streptomyces sp. strain PGA 64 and S. collinus, from which the genes responsible for rubromycin biosynthesis have recently been cloned (17), are known to produce rubromycins. A variety of sequences also cluster around the aureolic acid producer S. argillaceus, but it is not possible to propose boundaries for this group because there is no information about the compounds produced by the surrounding strains.…”
Section: Resultsmentioning
confidence: 99%
“…In an early example, Martin et al identified a cryptic PKS gene cluster in the genome of Streptomyces collinus by heterologous expression of the cluster in the first engineered host, S. coelicolor CH999 (266). More well-developed surrogate hosts have been derived in S. coelicolor and the industrial strain S. avermitilis.…”
Section: Heterologous Expression In Engineered Hostsmentioning
confidence: 99%
“…[116] codiert. Auf der Basis von putativen Genfunktionen und einem Shunt-Produkt oder Intermediat, Collinon (47), das über die Expression des unvollständigen Rubromycin-Biosynthese-Genclusters [117] erhalten wurde, sowie der Bildung von Lenticulon (48) in einer gezielten Oxygenase-Mutante, wurde ein Biosynthesemodell vorgeschlagen. [118] Diesem Modell zufolge werden auf dem Weg zum Spiro-Endprodukt nacheinander vier Kohlenstoff-Kohlenstoff-Bindungen gespalten.…”
Section: Aberrante Cyclisierung Aromatischer Polyketide (Favorskiiase)unclassified